FACTORS INFLUENCING GREEN ECONOMY DEVELOPMENT IN LAKE TOBA TOURISM AREA - Zulkarnain Nasution; Aziddin Harahap (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
The development of a green economy is a strategic issue in realizing sustainable development, especially in potential areas such as Lake Toba. However, the role of socio-cultural factors in supporting the green economy has not been extensively researched empirically. This study aims to analyze the influence of Community Awareness, Environmental Knowledge, and Local Cultural Beauty on Green Economic Development in the Lake Toba area. The method used is a quantitative approach with multiple linear regression analysis techniques with the help of SPSS software version 25. Data were obtained from questionnaires distributed to local respondents The results of the study showed that Community Awareness and Environmental Knowledge did not have a significant effect on the green economy, while the Beauty of Local Culture had a significant effect. The value of the determination coefficient (R²) of 0.4053 indicates that the three variables explain the 40.5% variation in the development of the green economy. These findings confirm the importance of a cultural approach in supporting the sustainability of the Lake Toba region.